The New Horizontal Worker: Privacy, Sexuality, and Professionalism in the Digital Bedroom - Heyes, Cressida; Haugen, Hannah (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2023)
In this essay we examine media coverage in 2020 and 2021 of the COVID-19-related practice of “working from bed.” Although presented as a new phenomenon, working from bed has a long history. We suggest that the late modern bourgeois understanding of the bedroom as a private space has long been manipulated by artists, writers, and other celebrities, both through staged photos and more self-conscious representation. These representations play on the paradox of a public figure making their intimate self visible and invite an audience without losing control of the scene. By contrast, media representation of (and advice about) working from bed for white-collar professionals is fraught with anxiety about how to create an image of a desexualized, generic worker whose bed, bedroom, and self-in-bed are newly available to clients, co-workers, and bosses. Presenting distinctive challenges for women workers, the advice we surveyed focuses on aesthetics and comportment, using “professionalism” as a code for discipline and trivializing the consequences of home surveillance.